PEMBUATAN MOCAF (MODIFIED CASSAFA FLOUR) DENGAN PROSES FERMENTASI MENGGUNAKAN BEBERAPA JENIS RAGI (Jurnal Pelangi : Research of Education and Development, 2014)
Cassava is tropical plants, productive and easily cultivated so it is expected to be one of the solutions to improve Indonesia's national food security. Mocaf is fermented cassava flour products using microorganisms. Mocaf is expected to replace the use of wheat flour which its necessity is escalated through the ages, while the area of wheat as a raw material is not fitted the climate of Indonesia. This research performed some sort of branded food yeast for producing Mocaf, taken for instance Fermipan, Saf-Instant yeast, tempe raprima yeast, tapai yeast, and unbranded bread yeast. It also would be analyzed the effect of soaking cassava with salt before fermentation, to nutrients generated by Mocaf. The objective of this research was knowing the types of yeast and fermentation process that is best in improving the nutritional quality of Mocaf. The best produced Mocaf in this research was made from fermented Mocaf using tapai yeast which was soaked with salt. It produced the highest level of protein i.e 40.860%, with low water levels i.e 6.640 %.